2016
DOI: 10.1080/15384101.2016.1149273
|View full text |Cite
|
Sign up to set email alerts
|

B-cell lymphoma 6 promotes proliferation and survival of trophoblastic cells

Abstract: Preeclampsia is one of the leading causes of maternal and perinatal mortality and morbidity and its pathogenesis is not fully understood. B-cell lymphoma 6 (BCL6), a key regulator of B-lymphocyte development, is altered in preeclamptic placentas. We show here that BCL6 is present in all 3 studied trophoblast cell lines and it is predominantly expressed in trophoblastic HTR-8/SVneo cells derived from a 1 st trimester placenta, suggestive of its involvement in trophoblast expansion in the early stage of placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…Related to this, here we demonstrated that in vivo HIF-1α interference leads to a lower expression of miR-127-3p and, consequently, increased expression of its target gene Bcl6, a transcriptional repressor involved in apoptosis31 and survival regulation32. Previous results of our lab demonstrated that miR127-3p is regulated by HIF-1α during proximal epithelial cell response to ischemia and it is a protector mechanism against renal ischemic injury13.…”
Section: Discussionsupporting
confidence: 76%
“…Related to this, here we demonstrated that in vivo HIF-1α interference leads to a lower expression of miR-127-3p and, consequently, increased expression of its target gene Bcl6, a transcriptional repressor involved in apoptosis31 and survival regulation32. Previous results of our lab demonstrated that miR127-3p is regulated by HIF-1α during proximal epithelial cell response to ischemia and it is a protector mechanism against renal ischemic injury13.…”
Section: Discussionsupporting
confidence: 76%
“…Western blot analysis was performed as previously described [53, 63]. Following antibodies were used: Mouse monoclonal antibodies against cyclin B1, Plk1 and p53 (Santa Cruz).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as reported (Muschol-Steinmetz et al, 2016;Steinhauser et al, 2017), using mouse monoclonal antibodies against cyclin B1 (#sc-752) and b-actin (#sc-47778) from Santa Cruz Biotechnology (Heidelberg).…”
Section: Depolymerization Assays Sag Stimulation Cell Viability Anmentioning
confidence: 99%